Aetiological heterogeneity of asymptomatic hyperglycaemia in children and adolescents - Feigerlová, Eva; Průhová, Štěpánka; Dittertová, Lucie; Lebl, Jan; Pintérová, Daniela; Kološtová, Katarína; Černá, Milena; Pedersen, O; Hansen, T (European journal of pediatrics, 2006)
INTRODUCTION: Randomly estimated fasting hyperglycaemia in an asymptomatic individual may represent the first sign of pancreatic beta-cell dysfunction. OBJECTIVE: We aimed at specifying the genetic aetiology of asymptomatic hyperglycaemia in a cohort of children and adolescents. SUBJECTS AND METHODS: We analysed the aetiological diagnosis in 82 non-obese paediatric subjects (38 males) aged 0.2-18.5 years (median: 13.1) who were referred for elucidation of a randomly found blood glucose level above 5.5 mmol/l. In addition to fasting glycaemia and circulating levels of insulin and C-peptide, the subjects were tested by an oral glucose tolerance test and an intravenous glucose tolerance test and screened for mutations in the genes encoding glucokinase (GCK), HNF-1alpha (TCF1), Kir6.2 (KCNJ11) (if aged <2 years) and HNF-4alpha (HNF4A) (those with a positive family history of diabetes). RESULTS AND DISCUSSION: We identified 35 carriers of GCK mutations causing MODY2, two carriers of TCF1 mutations causing MODY3, one carrier of a HNF4A mutation causing MODY1 and one carrier of a KCNJ11 mutation causing permanent neonatal diabetes mellitus. Of the remaining patients, 11 progressed to type 1 diabetes mellitus (T1DM) and 9 had impaired glucose tolerance or diabetes mellitus of unknown origin. In 23 subjects, an impairment of blood glucose levels was not confirmed. We conclude that 39 of 82 paediatric patients (48%) with randomly found fasting hyperglycaemia suffered from single gene defect conditions, MODY2 being the most prevalent. An additional 11 patients (13%) progressed to overt T1DM. The aetiological diagnosis in asymptomatic hyperglycaemic children and adolescents is a clue to introducing an early and effective therapy or, in MODY2, to preventing any future extensive re-investigations.
Keywords: mutace; Analysis of Variance; Genetic Testing; glukózový toleranční test; Female; Infant; předškolní dítě; dítě; ženské pohlaví; Adolescent; Carrier State; lidé; Glucose Tolerance Test; Mutation; hyperglykemie; Diabetes Mellitus, Type 1; přenašečství; analýza rozptylu; prospektivní studie; Male; kojenec; Prospective Studies; Czech Republic; Child, Preschool; Hyperglycemia; genetické testování; Česká republika; Child; mužské pohlaví; mladiství; diabetes mellitus 1. typu; Humans